Currency and financial crises - lessons from the Asian crises for China? - Nicolas Schlotthauer (University of Würzburg, Department of Economics, 2000)
The Asian crises also led to a discussion about what China can learn from the destabilising developments observed in the neighbouring countries. The main intention of this paper is to focus on the probability whether China will also face a severe, financial and/or currency crisis. Two main conclusions evolve from the current economic conditions in China. First of all the danger of a currency crisis is not given for China as - apart from the still existing capital controls which avoided massive short-term capital inflows - the interest rate differential to the anchor currency (US) will not cause excessive short-term capital inflows and thus will not cause a destabilising volume of portfolio investments. Nonetheless a depreciation of the RMB Yuan is discussed in detail. In addition China should continue reforming its financial system by a deeper institutional foundation and solving the problem of bad loans the commercial banks are still struggling with. Reforms should start soon as further capital account liberalisation will raise foreign pressure and the costs of financing the higher debt caused by restructuring banks and enterprises.
Keywords: 330; China; Asian crises; currency crisis; financial crisis; financial system reform; currency depreciation; capital account liberalisation